Critical Global Citizenship Education: A Study on Secondary School Students - González-Valencia, Gustavo; Massip Sabater, Mariona; Santisteban Fernández, Antoni (Frontiers in Education, 2022)
This article describes a study conducted in Catalonia (Spain) that examines the dimensions of global citizenship education (GCE) that emerge when secondary school students analyse images taken from the digital platforms of the mainstream media. We followed a mixed methodology for the research. To analyse the data, we employed content analysis, in the form of descriptive and inferential statistics. The results show that students in the final year of compulsory secondary education (aged 15-16) have great difficulty with analysing the information and images contained in media from a global citizenship perspective. While students tend to adopt a perspective of social responsibility, they do not have the tools necessary for critical interpretation of social facts and problems; they are still less able to formulate arguments or make decisions relating to actions within the parameters of social justice.